Accounting for consumers’ preferences in the analysis of dietary recommendations - Cobiac, L; Irz, X; Leroy, P; Réquillart, V; Scarborough, P; Soler, L-G (Springer Nature, 2018)
Background/Objectives The goal of this article is to present and demonstrate the applicability of an original method to assess the economic and health impacts of compliance with food-based recommendations. The method takes account of consumers’ preferences and the associated adoption cost in the assessment of various recommendations. Subjects/Methods We combine an economic model of diet choice with an epidemiological model to compute the health impacts of dietary changes. To demonstrate the use of the method, we analyse the impacts of a 5% variation in the consumption of seven food groups taken separately: a 5% increase in consumption of fruits and vegetables (F&V;) and milk products; and a 5% decrease in consumption of red meat, all meats, salty/sweet products, ready meals and butter/cream/cheese. Results A recommendation, when adopted by consumers, generates important changes in the whole diet due to substitutions and complementarities among foods. All simulated recommendations have a positive impact on health. The F&V; recommendation has the largest impact on the number of DALYs averted, but the highest adoption cost for consumers, especially for low-income consumers. Alone, the change in energy intake explains from 71% to 98% of the DALYs averted induced by a recommendation. Conclusions Small increases in recommended foods have the potential of generating relatively significant health gains. Preference-driven substitutions among foods have a major effect on simulated health outcomes and should be included in the assessment of dietary recommendations, together with the adoption cost borne by consumers.